Moral Education Values of the Character Alina Suhita in the Novel Hati Suhita by Khilma Anis and Their Relevance to the Psychology of Religion - Rachmawati, Eni; Budi, Eka Setya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
This study analyzes the moral education values embodied in the character Alina Suhita in the novel Hati Suhita by Khilma Anis and examines their relevance to the psychology of religion. Using a qualitative library research approach, the primary data were obtained from the novel, supported by relevant scholarly sources on moral education and religious psychology. Data were collected through documentation and analyzed using content analysis to identify moral values reflected in the character’s attitudes, dialogues, and life experiences. The findings indicate that Alina Suhita represents key moral values such as patience, sincerity, perseverance, respect for parents and teachers, and reliance on God (tawakal). These values correspond to central concepts in the psychology of religion, including emotional regulation, internalization of religious teachings, and the formation of a mature religious personality. This study highlights the role of literary works as alternative media for strengthening character education within the framework of Islamic moral education.